Analisis Tingkat Risiko Kredit Pada PT. BPR Yaspis Dana Prima Tentena - Mamase, Anjelina; Taariwuan, Silvany Annatje; Kawani, Fredrik Bastian (Fakultas Ekonomi Universitas KristenTentena, 2024)
This research was conducted at PT. BPR Yaspis Dana Prima Tentena. This study aims to determine the level of ktedit risk at PT. BPR Yaspis Dana Prima Tentena. This research was conducted using data collection techniques including observation, documentation and interview techniques. The analysis method used by the author is a quantitative method using Credit Riks Ratio analysis. Primary data sources with interviews and questions and answers, as well as secondary data through references and collectibility report data for 2017-20121 PT. BPR Yaspis Dana PrimaTentena is the source of data used by the author. Based on the results of the analysis, it was concluded that Non-Performing Loan (NPL) loans at PT. BPR Yaspis Dana Prima Tentena decreased from 2017-2020 and in 2021 increased by 5.0%, so this shows that PT BPR Yaspis Dana Prima Tentena's Non-Performing Loan is classified as moderate according to Bank Indonesia regulations.